KRITIK TERHADAP PENERAPAN PASAL 156a KUHP DITINJAU DARI PERSPEKTIF KEHIDUPAN DEMOKRASI DI INDONESIA - Dian Andriasari, Dian (Veritas et Justitia, 2017)
Since long time every application of Article 156a of the Criminal Code has always caused social tension, social situation becomes very sensitive. These conditions lead to social conflicts. The issue of religion then became a commodity in the narrative of the mass media, into a debate. In the end in some cases, it always attributes the threat of democratic life. Conflict in the name of religion also surfaced, at least social tension raised after the Judge's decision by using the article. Religion is a problem that can not be separated from what should and what is real. These two things will continue to develop whereby dialectics may occur between them. If in the past religion was seen to be close to some elements of society, there was a growing tendency to recognize the differentiation between these elements and to legitimize the division of labor between the elements. But this differentiation is not accepted by all religious communities. The state's hegemony against religion is more often the legitimacy of violence and unilateral truth claims. Debate about it then led to a lot of interpretation, cross interpretation of the dispute then led to the court using the criminal justice system approach. Here is the Law as the result of social process, which should be studied as a social reality, indicating that there is a need to broaden the perspective, meaning not only to understand the rule of law from the point of logical consistency of the rules only, but also to be viewed from aspects of the process of human relations in society both individually and institutionally. Using the sociological juridical approach, the author tries to discuss how the effect of the application of article 156a of the Criminal Code in the life of democracy in Indonesia and how the prospect of future arrangement related to the formulation of religious offense in the perspective of ius constituendum.